Case Report: Optical coherence tomography to guide PCI of iatrogenic injury of the circumflex artery after minimally invasive mitral valve repair - Borzanovic, Dusan; Ilic, Ivan; Nikolic, Dusan; Stojanovic, Ivan (Frontiers in Cardiovascular Medicine, 2023)
We present a case of a 42-year-old man who suffered an iatrogenic injury to his left circumflex (Cx) coronary artery after mitral valve (MV) repair surgery. After the patient suffered from myocardial infarction without ST-segment elevation following minimally invasive MV surgery, we performed repeated coronary angiography and optical coherence tomography (OCT), which revealed severe coronary stenosis of the dominant Cx caused by intramural hematoma. In addition, we proceeded with percutaneous coronary intervention and stent implantation.